Beyond affinity: selection of antibody variants with optimal biophysical properties and reduced immunogenicity from mammalian display libraries. Issue 1 (1st January 2020) - Dyson, Michael R.; Masters, Edward; Pazeraitis, Deividas; Perera, Rajika L.; Syrjanen, Johanna L.; Surade, Sachin; Thorsteinson, Nels; Parthiban, Kothai; Jones, Philip C.; Sattar, Maheen; Wozniak-Knopp, Gordana; Rueker, Florian; et al.
ABSTRACT: The early phase of protein drug development has traditionally focused on target binding properties leading to a desired mode of therapeutic action. As more protein therapeutics pass through the development pipeline; however, it is clear that non-optimal biophysical properties can emerge, particularly as proteins are formulated at high concentrations, causing aggregation or polyreactivity. Such late-stage "developability" problems can lead to delay or failure in traversing the development process. Aggregation propensity is also correlated with increased immunogenicity, resulting in expensive, late-stage clinical failures. Using nucleases-directed integration, we have constructed large mammalian display libraries where each cell contains a single antibody gene/cell inserted at a single locus, thereby achieving transcriptional normalization. We show a strong correlation between poor biophysical properties and display level achieved in mammalian cells, which is not replicated by yeast display. Using two well-documented examples of antibodies with poor biophysical characteristics (MEDI-1912 and bococizumab), a library of variants was created based on surface hydrophobic and positive charge patches. Mammalian display was used to select for antibodies that retained target binding and permitted increased display level. The resultant variants exhibited reduced polyreactivity and reduced aggregation propensity. Furthermore, we show in the case of bococizumab that biophysically improved variants are less immunogenic than the parental molecule. Thus, mammalian display helps to address multiple developability issues during the earliest stages of lead discovery, thereby significantly de-risking the future development of protein drugs.